Erythema nodosum as a result of estrogen patch therapy for prostate cancer: a case report. (December 2015) - Coyle, Christopher; Mangar, Stephen; Abel, Paul; Langley, Ruth
Abstract Introduction Erythema nodosum is often associated with a distressing symptomatology, including painful subcutaneous nodules, polyarthropathy, and significant fatigue. Whilst it is a well-documented side-effect of estrogen therapy in females, we describe what we believe to be the first report in the literature of erythema nodosum as a result of estrogen therapy in a male. Case presentation A 64-year-old Afro-Caribbean man with locally advanced carcinoma of the prostate agreed to participate in a randomized controlled trial comparing estrogen patches with luteinizing hormone-releasing hormone analogs to achieve androgen deprivation, and was allocated to the group receiving estrogen patches. One month later he presented with tender lesions on his shins and painful swelling of his ankles, wrists, and left shoulder. This was followed by progressive severe fatigue that required hospital admission, where he was diagnosed with erythema nodosum by a rheumatologist. Two months after discontinuing the estrogen patches the erythema nodosum, and associated symptoms, had fully resolved, and to date he remains well with no further recurrence. Conclusion Trial results may establish transdermal estrogen as an alternative to luteinizing hormone-releasing hormone analogs in the management of prostate cancer, and has already been established as a therapy for male to female transsexuals. It is essential to record the toxicity profile of transdermal estrogen in men to ensure accurate safety information. This case report highlights a previously undocumented toxicity of estrogen therapy in men, of which oncologists, urologists, and endocrinologists need to be aware. Rheumatologists and dermatologists should add estrogen therapy to their differential diagnosis of men presenting with erythema nodosum.